(untitled) (Latakia University Journal -Medical Sciences Series, 2023)
* The importance and justification of the research: Benign prostatic hyperplasia is one of the most common diseases associated with symptoms of the lower urinary tract, as these symptoms appear in 50% of men over 50 years of age. . Treatment options range from drug therapies to invasive procedures Recently, it has been suggested to add tadalafil (5 mg) to tamsulosin (0.4 mg) for 3 months as one of the available options for relieving associated lower urinary tract symptoms. The need to find an effective treatment for patients with benign prostatic hyperplasia and the results of international studies, which were directed mostly to the safety and effectiveness of the participation of tadalafil 5 mg and tamsulosin 0.4 mg for a period of 3 months in treatment, and since no local study was previously conducted that shows the effectiveness of this participation, we directed to conduct this study * The Aim: Comparison of the effectiveness of a drug combination between tamsulosin 0.4 mg with tadalafil 5 mg and tamsulosin 0.4 mg alone in the management of lower urinary tract symptoms associated with benign prostatic hyperplasia according to the International Scale of Prostate Symptoms * Patients and methods: Study type: prospective pilot study The research sample consisted of (100) patients who attended the Urology Department and Clinic from 28/4/2022 to 28/ 4/2023 The patients’ ages exceeded (50) years, and the patients were divided into two groups, and each group consisted of (50) patients Pharmacotherapy (Tamsulosin) was applied only to the patients of the first group, and the drug treatment (Tamsulosin and Tadalafil) was applied to the patients of the second group. The first evaluation was done after (6) weeks and a final evaluation after (12) weeks. * Results: • The quality of life and the mean value of the quality of life index improved, and the degree of complaint decreased by continuing the combined treatment. • In combination therapy, the rate of improvement is better, especially if the prostate was smaller before treatment • In co-treatment, the percentage of improvement increases if the treatment period is increased • In co-treatment, the rate of improvement is higher if the complaint was of medium degree before starting treatment. *Recommendations and Suggestions: Conducting a survey and early investigation of cases of symptomatic benign prostatic hypertrophy and treating them to avoid exacerbation of symptoms and lack of bladder compliance As a result, the upper urinary tract is damaged Combination therapy of tamsulosin and tadalafil for benign prostatic hyperplasia with moderate to severe complaints Emphasis on continuing treatment for 12 weeks and not interrupting it to achieve the best improvement Periodic follow-up of co-treatment patients to assess the extent of benefit and improvement of symptoms Conducting more studies and research related to healthy prostate enlargement to reach the best standards and recommendations aimed at controlling symptoms and improving patients’ quality of life.